SISTEM KEWASPADAAN DINI (SKD) KLB DBD DI KABUPATEN SRAGEN - Pertiwi, Julia (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
Dengue Hemorrhagic Fever (DHF) is a viral disease that is transmitted by mosquitoes, so there is the potential for outbreak. The aim of this study are to determine the implementation of DHF’s outbreak response conducted by “Posko DBD Sragen”. The study design is case study using qualitative studies. Variables that are data collection and processing; data presentation and analysis; and conclusions and follow-up. The study was conducted in August - October 2019 with 6 respondents. “Posko DBD Sragen” is 35 units and reporting dengue cases regularly on the same day, the collection is done by Whats App group. Presentation of data using tabulations and combined with graphs to make it easy to do descriptive analysis. Data analysis has been carried out since making weekly tabulations, so that any abnormalities that occur in the work area can be immediately identified precautions. Presentation and analysis of data is done by analyzing people, places and times.